A feasibility study of organizing occupational health services for farmers. - Vohlonen, I. J.; Husman, Kaj; Kalimo, E.; Nuutinen, Juhani; Raitasalo, R.; Tupi, K.; Virolainen, R. (Scandinavian Journal of Work, Environment & Health, 1982)
In Finland the Occupational Health Care Act of 1979 provides farmers the possibility of purchasing occupational health services. The main objective of the present study is to develop national model for the organization of occupational health services for farmers. The problems of providing and specifying occupational health services for farmers can be described by two parameters. The first is the type of farm production. The occupational health services to be provided are though to depend on the occupational health risks. The risks vary with the type of farm production, which in turn depends on the geographic location of the farm. The second parameter represents the supply of occupational services to be provided by the municipal health center. The supply has been characterized as occupational health inspections of farms, health examinations, and health education. For the optimization of the supply and the demand, the experiment consists of three models to be tested in respect to two matrices of risk. The feasibility of the models in the 2-a experiment will be evaluated by pre- and postexperimental surveys.